Balanced Scorecard Method in Performance Audit of Budgetary Users (Vallis Aurea, 2020)
The paper aims to explore how the Balanced Scorecard method can improve budgetary users' performance audit in Croatia. Literature review on performance measurement in the Croatian public sector gives an overview of the development level in strategic planning, control, and monitoring performance. The paper gives some suggestions for improving Croatia's budget system based on the identified disadvantages and weaknesses in measuring and monitoring performance.